Análise das práticas de informática na educação da Escola Municipal Aloys João Mann - Cascavel/PR - Kaminski, Márcia Regina (2018)
The presence of Information and Communications Technology in education has been playing a key role due to its relevant contribution to teaching and learning processes, the development of students' autonomy, creativity and protagonism. With a particular interest in Digital Games, in Development of Computational Thinking, in Virtual Learning Environments and in Educational Robotics in first period of the Elementary Education system in Brazil, the general objective of this research was to investigate the contributions of these resources from the experiences of pedagogical practices in Computing classes at a municipal school in the city of Cascavel, Parana state, in order to replicate the projects carried out in other compatible realities, as well as the proposition of improvements and new possibilities of pedagogical application of different technological resources under the concepts of the theoretical framework. To carry out the study, a qualitative research was performed; for data collection, a bibliographic research and a descriptive and interpretive case study were carried out in two stages: (i) historical analysis of the projects developed in the school, difficulties for its implementation and form of organization of each one of them; (ii) observation of the activities and surveys with the principal, the pedagogical coordination, the instructor of Educational Robotics, teachers and parents of students involved in each one of the analyzed projects, in order to verify the impacts that these projects have produced for the teaching and learning processes of this school. The data were analyzed and interpreted by means of the codification of the answers in the surveys, as well as the data collected during the observation of the computer classes in which digital games were used, proposals for the development of computational thinking, robotics and for the monitoring and evaluation of the virtual learning environments used by the school as an incentive to extra-class study habits. The results show that the school has adopted different practices, based on a perspective of interactivity, autonomy and production by the students, aligned to the cyberculture context, including the ICT beyond pedagogical resources, that is, as cultural artifacts that should be part of the contexts in order to present possibilities of pedagogical work that involve the protagonism, the autonomy and the creativity of the students through its use.